Post-traumatic stress disorder among refugees following xenophobic attacks in Durban, South Africa - Womersley, Gail; Shroufi, Amir; Severy, Nathalie; van Cutsem, Gilles (Lisbon: inScience Press, 2018)
Following a spate of xenophobic attacks against foreign nationals in Durban, South Africa, displacement camps were set up to shelter predominantly Congolese and Burundian refugees. Embedded within the emergency program a prevalence study of symptoms of posttraumatic stress disorder (PTSD) was conducted among a convenience sample of this population. Twenty-seven participants included men and women who were screened for symptoms using the Harvard Trauma Questionnaire (HTQ). Results indicate a prevalence rate of 85% among this population. Limitations include the small sample size and potential self-reporting. The high prevalence rate of people who meet diagnostic criteria for PTSD has profound implications for psychosocial interventions and access to mental health services for this community – as well as significant broader legal and social justice implications.
Keywords: PTSD; refugees; trauma; cross-cultural.